(untitled) (Revista Electrónica REDINE, 2018)
The following investigation has as a main purpose to show the importance and relevance of the Classical Method in Latin teaching. This article is a documental investigation which exposes fundamental concepts; principles; techniques, such as: translation from a literary text, reading comprehension questions, perfect composition, and memorization; and finally inductive, deductive and analytical procedures regarding to Latin teaching through the usage of the Classical Method. All of these aspects were taken thoroughly from both extensive documental materials as specialized books and magazines and important electronic fountains. Furthermore, it will be really useful by educating students in relation to the optimization of their memorization, development of the logic thinking and development of the effective communication. It is important to mention that a class plan in Latin language, using the Classical Method will be added at the end of this investigation.